The Relationship between Student Discipline Attitudes and a Child Friendly School Environment - Nahuda; Soleh , Muhamad (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to obtain precise, correct, valid reliable and reliable data about the Influence of a Child-Friendly School Environment on Student Discipline at SMAN 107 East Jakarta, How much influence between the two is sufficient or moderate and the factors that influence it. This study used the "descriptive analytic koreanal" method while the objects of research were students of class X IPA 1, X IPA 2 and X IPS 2, X IPS 3 at SMAN 107 East Jakarta, totalling 590 students. data collection techniques using questionnaires and tests of 118 respondents. Also equipped with observation techniques and interviews. Meanwhile, in analyzing the data using Product Moment from Karl Pearson. The results of the study are that when viewed in terms of the product-moment coefficient test it produces rxy or ro of 0.511. This shows that ro is greater than rt at a significant level of 5% = 0.174 and smaller than rt at a significant level of 1% = 0.228. Comparing the magnitude of "rxy" with "rt", as is known, the rxy that the researchers obtained was 0.511 while the rt was 0.174 and 0.228, respectively. Thus it turns out that rxy ? rt at a significant level of 5% and rxy ? rt at a significant level of 1%. In this case, it means that there is an Influence of the Child-Friendly School Environment on Student Discipline, the effect is sufficient. This correlation is that discipline is very much needed in a Child-Friendly School Environment